Conflicting Climate Change Frames in a Global Field of Media Discourse - Broadbent, J. (2016)
Reducing global emissions will require a global cosmopolitan culture built from detailed attention to conflicting national climate change frames (interpretations) in media discourse. The authors analyze the global field of media climate change discourse using 17 diverse cases and 131 frames. They find four main conflicting dimensions of difference: validity of climate science, scale of ecological risk, scale of climate politics, and support for mitigation policy. These dimensions yield four clusters of cases producing a fractured global field. Positive values on the dimensions show modest association with emissions reductions. Data-mining media research is needed to determine trends in this global field